56. KNOWLEDGE AND PRACTICES REGARDING DENGUE HEMORRHAGIC FEVER PREVENTION AND CONTROL AMONG RESIDENTS IN HOC MON DISTRICT, HO CHI MINH CITY IN 2025 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Background: Dengue hemorrhagic fever continues to pose a significant global public health threat. The disease not only endangers patients’ health and lives, adversely affecting their psychological well-being and that of their families, but also leads to economic and social burdens, thereby increasing the risk of poverty.Objective: This study aims to describe the current status of knowledge and practices concerning dengue hemorrhagic fever prevention and control among residents in Hoc Mon district, Ho Chi Minh city in 2025, and to identify related factors.Method: A descriptive cross-sectional study was conducted on 350 household heads or household representatives aged 18 years and above residing in Hoc Mon district. Data were collected through structured interviews using standardized questionnaires and direct household observations via monitoring checklists.Results: The proportion of residents with adequate knowledge and appropriate practices regarding DHF prevention and control was 66.0% and 47.4%, respectively. Household economic status and the number of information sources accessed about Dengue hemorrhagic fever were statistically related to overall knowledge (p < 0.05). Furthermore, overall knowledge was significantly related to preventive practices regarding Dengue hemorrhagic fever prevention and control (p < 0.001).Conclusion: The findings indicate that the level of appropriate knowledge and practices related to Dengue hemorrhagic fever prevention and control among residents in Hoc Mon district remains suboptimal. It is necessary to enhance health education and communication efforts through integrated and continuous strategies, employing diverse approaches, particularly targeting low-income households.s, employing diverse approaches, particularly targeting low-income households.
Keywords: Dengue hemorrhagic fever; knowledge; practices; Hoc Mon.